Charismatic Nonverbal Displays by Leaders Signal Receptivity and Formidability, and Tap Approach and Avoidance Motivational Systems - Keating, Caroline F.; Adjei Boateng, Fiona; Loiacono, Hannah; Sherwood, William; Atwater, Kelsie; Hutchison, Jaelah (Frontiers in Psychology, 2020)
Status cues and signals act as guidance systems by regulating social approach and avoidance. Applied to leadership, we hypothesized that nonverbal displays conveying the dual status messages of receptivity and formidability, and the approach/avoidance motives they activate, set conditions for charismatic, leader-follower relationships. We investigated perceptions of charisma, the nonverbal signals associated with them, the motives they energize, and the relationships they support across levels-of-analysis. At the social-perceptual level (Studies 1a-d), eligible voters rated political leaders’ traits after viewing silent, 30-second videos of speeches presented online. As predicted, perceptions of politicians’ receptivity (warmth and attractiveness) and formidability (competence and power) were independently associated with perceptions of their charisma; perceptions of trustworthiness and authenticity showed weak or negligible associations. Results were similar when the stimuli were female, Jamaican educational leaders. Leaders’ nonverbal behavior was linked to perceptions of their receptivity, formidability, and charisma in Study 2. At the brain-systems level, Studies 3a-b tested predictions that charismatic nonverbal performances stimulate equivalent degrees of approach and avoidance motivation in observers. Brain recordings via electroencephalography (EEG) were made while undergraduates viewed leaders rated high or low in charisma. Discrepancies in alpha activity in the left and right frontal hemispheres (associated with approach and avoidance, respectively) were relatively diminished when participants viewed highly charismatic political leaders, indicating that approach and avoidance motives are energized in response to charismatic performances. EEG patterns for Jamaican leaders were similar but not significant. At the group level-of-analysis, Study 4 sought evidence that charismatic leaders create uniquely influential relationships with followers. Video recordings of student leaders interacting with pairs of unfamiliar students during a group decision-making task were assessed for leader receptivity, formidability, and charisma by independent sets of undergraduate judges. Perceptions of student leaders’ receptivity and formidability predicted their charisma, and charismatic leaders were most effective in bringing followers to privately (but not publicly) accept a controversial group decision. Across studies, evidence generally supported hypotheses generated from status cues theory: charismatic leadership builds upon the nonverbal projection of dual status messages and the approach/avoidance motives they engender, setting conditions for a uniquely powerful brand of influence.